Use of 'stacked' dermal template: Biodegradable temporising matrix to close a large myelomeningocele defect in a newborn - Saiidy Hasham; Ciaran O'Boyle; Skaria Alexander (SAGE Publishing, 2024)
Background Myelomeningocele is a severe and complex congenital malformation of the central nervous system. Failure of neural tube closure at around four weeks of gestation results in an open communication between the neural placode and the external environment with varied functional impairment. Surgery is usually required. Objectives The primary goals of surgical management are to preserve neural function and minimise infection. Reconstruction is dependent upon the site and size of the defect as well as the quality of the surrounding soft tissues. Surgeons may employ a range of reconstructive techniques in order to achieve closure. Skin substitutes, also known as dermal regeneration templates, have also been utilised. Discussion In our unit, we use NovoSorb Biodegradable Temporising Matrix to reconstruct full-thickness skin and soft tissue defects. It is a synthetic, biodegradable, dermal regeneration template, composed of polyurethane foam bonded to a transparent sealing membrane and typically requires a two stage reconstruction. Integration and vascularisation take approximately three weeks. After this time, the recipient wound bed is suitable for split thickness skin grafting. A further benefit of dermal regeneration templates is the possibility of 'stacking' layers, which serves to increase the thickness of the final construct and to minimise overall contour defects. The authors present the case of a one-day-old full-term neonate with a large lumbosacral myelomeningocele that was successfully managed with staged, stacked NovoSorb Biodegradable Temporising Matrix and split thickness skin grafting. The authors believe this is the first case in which a 'stacked' dermal regeneration templates has been used to achieve healing of a primary myelomeningocele defect. Lay Summary Background: NovoSorb Biodegradable Temporising Matrix (BTM) is a dermal regeneration template (DRT) and is used to reconstruct wounds following full-thickness skin and soft tissue loss resulting from burn injury, trauma, infection or surgery. It is composed of 2-millimetre thick, synthetic, biodegradable polyurethane foam bonded to a transparent (non-biodegradable) sealing membrane. Like all DRTs, it acts as a scaffold for cellular integration and vascularisation to eventually form a 'neo-dermis'. This is usually apparent from around three weeks. A second stage procedure can then be performed, with removal of the outer sealing membrane and split thickness skin grafting of the vascularised layer. Objectives: Myelomeningocele is a severe and complex congenital malformation of the central nervous system and forms the group of anomalies commonly referred to as neural tube defects (NTDs). Neural tube closure usually occurs at around four weeks of gestation and failure to do so, results in an open communication between the neural placode and the external environment. The degree of functional impairment varies but can include: lower limb paralysis; sensory loss; bladder and bowel dysfunction. In order to preserve neural function and minimise the risk of infection, surgery is usually required to close the defect. Reconstruction is varied and is dependent upon the site and size of the defect as well as the quality of the surrounding soft tissues. The use of local flaps has the potential complication of skin necrosis. Muscle based flaps may be debilitating and limit future functionality and worsen postural development. We were presented with a one-day-old neonate with a large lumbosacral myelomeningocele. A DRT (NovoSorb BTM) was selected as the primary reconstruction. Firstly, selection provided relatively low risk, with minimal morbidity and preserved the full complement of flap based reconstructive options for a later stage should instrumentation be required. Secondly, NovoSorb BTM conferred a robust seal over the dural repair with no demonstrable cerebrospinal fluid leak. Thirdly, the ability to add layers ('stack') of NovoSorb BTM in stages, once integration and vascularisation of the previous layer is complete, allows reconstruction of deeper contour defects. Discussion: We have illustrated the successful use of NovoSorb BTM as a DRT to achieve closure of a large lumbosacral myelomeningocele without complication and with longstanding stability. We believe this technique provides reconstructive teams with an alternative option that is effective, safe and reproducible and which spares local tissues for future elective reconstructive procedures, should they be required.